STRATEGI ADAPTIF GURU MENGHADAPI TRANSFORMASI PEMBELAJARAN DI ERA SOCIETY 5.0 DI SMP NEGERI 1 LORE BARAT - Indah Suarni; Intan Permatasari (Scolae: Journal of Pedagogy, 2026)
The transformation of learning in the Society 5.0 era requires teachers to integrate digital technology with pedagogical approaches to create innovative, adaptive, and student-centered learning environments. However, its implementation in rural schools continues to face significant challenges, particularly in terms of digital infrastructure and teachers' digital competencies. This study aimed to analyze the challenges encountered by teachers and identify the strategies they employ in adapting to learning transformation in the Society 5.0 era at SMP Negeri 1 Lore Barat. This research employed a quantitative descriptive approach. The population consisted of all 13 teachers at SMP Negeri 1 Lore Barat, and a total sampling technique was applied, whereby all teachers were included as research participants. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed through descriptive statistics, including mean scores and standard deviations, using IBM SPSS Statistics Version 26. The findings revealed that the level of challenges faced by teachers was categorized as moderate, with a mean score of 3.40, while teachers' strategies in responding to learning transformation were categorized as high, with a mean score of 4.18. The primary challenges included limited internet connectivity, inadequate technological facilities, and insufficient professional development opportunities related to digital competencies. Meanwhile, the dominant strategies involved continuous professional development through training, self-directed learning, the development of digital learning media, and collaborative practices among teachers. The study concludes that the successful implementation of learning transformation in the Society 5.0 era depends not only on the availability of digital technology but also on teachers' professional readiness, institutional support, and educational policies that strengthen digital infrastructure and teachers' competencies.